Study on the spatio-temporal evolution and multi-scale influencing factors of digital technology innovation: A case study of 41 cities in the Yangtze River Delta(数字技术创新的时空演进与多尺度影响因素研究——以长三角地区41个城市为例) - 李云霞(LI Yunxia); 高世杰(GAO Shijie); 李羚锐(LI Lingrui) (Zhejiang Daxue xuebao. Lixue ban, 2025)
It is worth focusing on the development trend, spatial pattern, and multi-scale effects of digital technology innovation which is the core engine driving the development of the digital economy. Based on the digital technology patent data of 41 cities in the Yangtze River Delta region from 2016 to 2021, the above focuses of concern were analyzed using kernel density estimation, Moran index, spatial Markov chain, geographically weighted regression model and multi-scale geographically weighted regression model. The study finds that: (1) The spatial characteristics of digital technology innovation activities in the Yangtze River Delta region show a "reverse E-shape", with Shanghai and Hangzhou as the high points, and the positive spatial clustering of "high agglomeration-low surrounding" for other cities. There is no obvious trend of multidimensional polarization. (2) The spatial Markov chain analysis shows a "club convergence" phenomenon in the dynamic regional change of digital technological innovation within the Yangtze River Delta region. (3) The multi-scale geographically weighted regression model shows that the degree of openness to the outside world and the level of logistics development have small spatial scales and are local factors, while the industrial structure, the level of infrastructure, environmental regulation, and employment structure are global factors. Therefore, in addition to the global factors, the policy of promoting digital technological innovation in prefecture-level cities should also focus on improving the level of openness to the outside world and the level of logistics development.数字技术创新是推动数字经济发展的核心引擎，其发展趋势、空间格局与在不同空间尺度上的影响因素亟需深入研究。基于长三角地区41个城市2016—2021年的数字技术专利数据，采用核密度估计、莫兰指数、空间马尔可夫链、地理加权回归（geographically weighted regression，GWR）模型和多尺度地理加权回归（multi-scale geographically weighted regression，MGWR）模型对数字技术创新的分布格局、演进态势和多尺度效应展开了分析。研究发现：（1）长三角地区数字技术创新的空间分布特征呈现“反E形”结构，以上海市和杭州市为高点，城市间保持“高高集聚-低低相邻”的正向空间集聚性，未出现明显的多维极化现象。（2）空间马尔可夫链分析表明，在长三角地区数字技术创新动态区域变化过程中，存在“俱乐部趋同”现象。（3）MGWR模型的拟合结果显示，对外开放程度和物流发展水平具有较小的空间尺度，属于局部因素，而产业结构、基础设施水平、环境规制和就业结构属于全局因素。因此，在城市数字技术创新水平提升路径中除需关注全局因素外，还应注重提升对外开放程度和物流发展水平，以推动地方创新水平的提升。